Consumo de café segundo métodos de preparo e associação com perfil lipídico sérico em hipertensos e diabéticos de Flexeiras AL. - Lima, Fabiana Accioly de (2008)
The cardiovascular diseases consist of a public health problem of determined by a complex network of risky factors, with distinction to those related to the life style. Coffee consumption has been pointed out as one of these factors, based on the proposal of which the diterpenes there present would raise the cholesterol and serum triglycerides, one of the most important factors of cardiovascular risk. In this context, objectifying to contribute in the discussion of this problem in focus, this dissertation presents two articles: a revision of literature concerning substances present in the coffee drink and its relation to the systemic arterial and dyslipidemias hypertension, and an original article that presents a transversal study where the association between the consumption of coffee and serum lipid profile in hypertensions and diabetics type 2 were verified. Studies on the identification of substances present in coffee and the relation of many of them to the health have been growing in the last few decades, which is understood because of the fact that coffee is one of most popular drinks, world-widely consumed, as well as for its economic importance in Brazil and in the European countries. The caffeine, mainly the cafestol and kahweol diterpenes and the chlorogenic acids are the composites most discussed in this dissertation. Emphasis is given to the preparation methods of the coffee drink, consumption and dilution, and the possible relation of these factors with the serum lipid profile and dyslipidemias.